MIGRATION PATTERN IN PAYMENT PREFERENCES POST COVID-19 AMONG CONSUMERS IN MALAYSIA (Journal of Economics and Sustainability, 2025)
The purpose of this study is to explore the patterns of migration in consumer payment preferences and to investigate the pattern of changes in payment preferences of daily transactions by type and value of transactions and to compare consumers’ overall perception of the selected common retail payment methods. A total of 407 responses were collected through an online survey. Logistic regression was used to determine the factors that can significantly influence consumers’ migration of payment preferences. The findings of the study show that Cash to E-wallets is the biggest shift in payment preference, lower-income consumers are less likely to change their payment preferences and the biggest change in payment preferences in the type of transactions were transactions in food stalls and convenience stores. Furthermore, the highest shift away from cash to E-wallets was in transactions below RM100 while a significant shift from cash to cards payments was for transactions above RM100. Economic factors such as income and technological receptiveness proxied by age have significant influence on the changes in payment preferences during crises. The observed shifts in preferences suggest inherent differences in the features and functionalities offered by various payment methods. This study sheds light on the migration trends in payment preferences, highlighting the unique characteristics of various payment methods. Understanding consumer perceptions of these methods can help payment providers to develop and promote targeted solutions.